2009
DOI: 10.1016/j.renene.2008.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Design and performance of a transportable hemispherical solar still

Abstract: a b s t r a c tA simple transportable hemispherical solar still was designed and fabricated, and its performance was experimentally evaluated under outdoors of Dhahran climatic conditions. It was found that over the hours of experimental testing through daytime, the daily distilled water output from the still ranged from 2.8 to 5.7 l/m 2 day. The daily average efficiency of the still reached as high as 33% with a corresponding conversion ratio near 50%. It was also found that the average efficiency of the stil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(28 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…Solar stills can be classified into active and passive solar stills. Many papers have studied more specific characteristics of solar stills with various configurations, hemispherical solar stills [4], spherical solar still [5], pyramidal solar still [6], double-basin solar still [7][8][9][10][11], vacuum solar still [12], compound parabolic concentrator (CPC) solar still [5], wick type solar still [13], triple basin solar still [14], multiple basin solar still [15,16], inverted absorber solar still [17][18][19][20], tubular solar stills [20][21][22][23], solar still coupled with solar collectors, and thermal storage [24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Solar stills can be classified into active and passive solar stills. Many papers have studied more specific characteristics of solar stills with various configurations, hemispherical solar stills [4], spherical solar still [5], pyramidal solar still [6], double-basin solar still [7][8][9][10][11], vacuum solar still [12], compound parabolic concentrator (CPC) solar still [5], wick type solar still [13], triple basin solar still [14], multiple basin solar still [15,16], inverted absorber solar still [17][18][19][20], tubular solar stills [20][21][22][23], solar still coupled with solar collectors, and thermal storage [24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 listed the efficiencies of different types of passive solar still from the past researchers. [22] Single slope solar still 34% Taamneh and Taamneh, 2012 [23] Pyramidal solar still 30% Ismail, 2009 [24] Hemispherical solar still 33% Abdullah, 2013 [25] Stepped solar still 48% Dashtban and Tabrizi, 2011 [10] Weir cascade solar still 47%…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been reported on the physical and operational aspects of solar stills with most reporting on methods which may be introduced in order to enhance the productivity of stills [1][2][3][4][5][6][7][8][9], while very few discussed the quality of the distillate http://dx.doi.org/10.1016/j.jhazmat.2014.08.003 0304-3894/© 2014 Elsevier B.V. All rights reserved. resulting from these stills.…”
Section: Introductionmentioning
confidence: 99%